An Analysis of Students’ Collocation Translation in EFL Classroom - Ira Maisarah; Indri Febriana (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2021)
This study sought to answer the question,